2012
DOI: 10.2478/v10078-012-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Related Differences in Force-Velocity Characteristics of Upper and Lower Limbs of Competitive Adolescent Swimmers

Abstract: While there is a direct relationship between maximal anaerobic power (Pmax) and swimming performance, the relationship between upper and lower limbs with regard to Pmax and force-velocity (F-v) characteristics is not clear. The aim of the present study was to examine the effect of age and sex on the ratios of mechanical characteristics between upper and lower extremities of adolescent swimmers. Seventeen girls (aged 14.7±1.8 yr) (mean±standard deviation) and 28 boys (14.6±1.4 yr), all members of competitive sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…However, a number of studies have suggested that a better fit of F-V relationship of various maximum performance multi-joint movements could be a liner one, at least within moderate ranges of F (typically manipulated by varying external loads) and corresponding V . Such results have been obtained from maximum effort squats and vertical jumps [(Vandewalle et al 1987; Rahmani et al 2001; Sheppard et al 2008); see also further text for details], cycling (Driss et al 2002; Driss and Vandewalle 2013; Nikolaidis 2012), simultaneous leg extensions against various dynamometers and sledge devices (Yamauchi et al 2009; Samozino et al 2012, 2014), running (Jaskolska et al 1999; Morin et al 2010), or arms and upper body movements (Hintzy et al 2003; Nikolaidis 2012). Note that F here corresponds to externally measured force, while V is the velocity of the moved center of mass (i.e., body mass and/or external mass).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, a number of studies have suggested that a better fit of F-V relationship of various maximum performance multi-joint movements could be a liner one, at least within moderate ranges of F (typically manipulated by varying external loads) and corresponding V . Such results have been obtained from maximum effort squats and vertical jumps [(Vandewalle et al 1987; Rahmani et al 2001; Sheppard et al 2008); see also further text for details], cycling (Driss et al 2002; Driss and Vandewalle 2013; Nikolaidis 2012), simultaneous leg extensions against various dynamometers and sledge devices (Yamauchi et al 2009; Samozino et al 2012, 2014), running (Jaskolska et al 1999; Morin et al 2010), or arms and upper body movements (Hintzy et al 2003; Nikolaidis 2012). Note that F here corresponds to externally measured force, while V is the velocity of the moved center of mass (i.e., body mass and/or external mass).…”
Section: Introductionmentioning
confidence: 86%
“…For example, the relationship could be effectively used in movement modeling and optimization, such as regarding the optimality of the F-V profile to provide the maximum performance jumps (Samozino et al 2012; Samozino et al 2013), or for exploring the mechanisms responsible for bilateral deficit (Samozino et al 2014). Loaded vertical jumps and other multi-joint maximum performance tasks could also provide linear F-V relationships that could enable a comprehensive assessment of the muscular F, V , and P , generating capacity in various populations, as well as the assessment of the effectiveness of various athletic training and rehabilitation interventions (Yamauchi et al 2009; Nikolaidis 2012; Cormie et al 2011; Driss and Vandewalle 2013). …”
Section: Introductionmentioning
confidence: 99%
“…These relationships have been routinely presented in standard textbooks of biomechanics, muscle physiology, or motor control [c.f., (McMahon 1984)]. However, more recent studies have suggested that the F-V relationship of maximum performance multi-joint tasks could be approximately linear, such as when obtained from leg extensions where leg muscles act through closed kinetic chains (Samozino et al 2012(Samozino et al , 2014bYamauchi et al 2009), cycling (Driss and Vandewalle 2013;Nikolaidis 2012;Ravier et al 2004), vertical jumps (Cuk et al 2014;Rahmani et al 2001;Samozino et al 2014a;Sheppard et al 2008;Vandewalle et al 1987), or upper body movements (Nikolaidis 2012;van der Tillar 2004;Hintzy et al 2003;Sprague et al 2007;Cronin et al 2003). Note that the results have been obtained from either the maximum (Vandewalle et al 1987;Rahmani et al 2001;Hintzy et al 2003) or mean F and V data (Samozino et al 2012(Samozino et al , 2014aRavier et al 2004), or both (Cuk et al 2014;Sprague et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, to use these models either to study the fundamental properties of the human musculoskeletal system [c.f., (Bobbert 2012;Samozino et al 2012;Jaric and Markovic 2013)] or to develop routine tests for physical abilities (Cronin et al 2003;Nikolaidis 2012;Ravier et al 2004), the linearity of the F-V relationship needs to be evaluated, while its parameters need to be both reliable and valid. However, although the applied linear models usually revealed a strong relationship (Cuk et al 2014;Hintzy et al 2003;Ravier et al 2004;Yamauchi and Ishii 2007;Samozino et al 2014a), only one study has directly compared the linear and polynomial models applied on the recorded F and V data (Cuk et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It seems impossible that women could outperform men in ultra-triathlons as presented by Coast et al for running 31. Potential reasons to explain why men are faster than women in endurance performance are the higher power in upper and lower limbs in men compared to women 32,33…”
Section: Discussionmentioning
confidence: 99%